Narrative Review: Quantitative EEG in Disorders of Consciousness - Betty Wutzl; Stefan M. Golaszewski; Kenji Leibnitz; Patrick B. Langthaler; Alexander B. Kunz; Stefan Leis; Kerstin Schwenker; Aljoscha Thomschewski; Jürgen Bergmann; Eugen Trinka (Brain Sciences, 2021)
In this narrative review, we focus on the role of quantitative EEG technology in the diagnosis and prognosis of patients with unresponsive wakefulness syndrome and minimally conscious state. This paper is divided into two main parts, i.e., diagnosis and prognosis, each consisting of three subsections, namely, (i) resting-state EEG, including spectral power, functional connectivity, dynamic functional connectivity, graph theory, microstates and nonlinear measurements, (ii) sleep patterns, including rapid eye movement (REM) sleep, slow-wave sleep and sleep spindles and (iii) evoked potentials, including the P300, mismatch negativity, the N100, the N400 late positive component and others. Finally, we summarize our findings and conclude that QEEG is a useful tool when it comes to defining the diagnosis and prognosis of DOC patients.